Heat transfer enhancement of TiO2/water nanofluid in a heat exchanger tube equipped with overlapped dual twisted-tapes - S. Eiamsa-ard; K. Kiatkittipong; W. Jedsadaratanachai (My University, 2015)
Titanium dioxide (TiO2) in water as nanofluid was employed for heat transfer enhancement together with overlapped dual twisted tapes (O-DTs). The study encompassed Reynolds numbers from 5400 to 15,200, O-DTs with overlapped twist ratios (yo/y) of 1.5, 2.0 and 2.5 and nanofluids with TiO2 volume concentrations (ϕ) of 0.07%, 0.14% and 0.21%. The experimental and numerical results indicated that O-DTs with smaller overlapped twisted ratio delivered a stronger swirl intensity and higher turbulent kinetic energy (TKE). The use of O-DTs at the smallest overlapped twist ratio of 1.5 enhanced heat transfer rates up to 89%, friction factor by 5.43 times and thermal performance up to 1.13 times as compared to those of plain tube. In addition, heat transfer increased as TiO2 volume concentration of nanofluid increased, owing to the increases of contact surface and thermal conductivity. The simultaneous use of the O-DTs having twist ratios 1.5 with the nanofluid with TiO2 volume concentration of 0.21% resulted in heat transfer enhancement around 9.9–11.2% and thermal performance improvement up to 4.5% as compared to the use of O-DTs alone. The empirical correlations of heat transfer rate (Nu), friction factor (f) and thermal performance (η) in a constant wall heat flux tube equipped O-DTs at different overlapped twist ratios (yo/y) and volume concentrations of TiO2 nanoparticles (ϕ) are also reported for heat transfer applications.
Keywords: Heat transfer enhancement; Enhanced heat transfer; Nanofluid Flow and Heat Transfer